Fucoxanthin from microalgae Phaeodactylum tricornutum inhibits pro-inflammatory cytokines by regulating both NF-kappa B and NLRP3 inflammasome activation - Lee, A-Hyeon; Shin, Hye-Yoon; Park, Jong-Hwi; Koo, Song Yi; Kim, Sang Min; Yang, Seung-Hoon (Nature Publishing Group, 2021)
Pro-inflammatory cytokines such as IL-1 beta, IL-6, and TNF-alpha are mediated by the activation of various kinds of signaling pathways in the innate immune system. Particularly, NF-kappa B and NLRP3 inflammasome signaling are involved in the production and secretion of these cytokines. Each signaling is participated in the two steps necessary for IL-1 beta, a representative pro-inflammatory cytokine, to be processed into a form secreted by cells. In the priming step stimulated by LPS, pro-IL-1 beta is synthesized through NF-kappa B activation. Pro-IL-1 beta cleavages into mature IL-1 beta by formed NLRP3 inflammasome in the activation step induced by ATP. The mature form of IL-1 beta is subsequently secreted out of the cell, causing inflammation. Moreover, IL-6 and TNF-alpha are known to increase in NLRP3 inflammasome-mediated conditions. Here, we found that fucoxanthin, one of the major components of Phaeodactylum tricornutum, has an inhibitory effect on NF-kappa B and NLRP3 inflammasome activation induced by the combination of LPS and ATP in bone marrow-derived immune cells as well as astrocytes. Fucoxanthin, which is abundant in the EtOH fraction of Phaeodactylum tricornutum extracts, has shown to have less cell toxicity and found to decrease the production of major pro-inflammatory cytokines such as IL-1 beta, IL-6, and TNF-alpha. Fucoxanthin has also shown to suppress the expression of cleaved caspase-1 and the oligomerization of ASC, which are the main components of the NLRP3 inflammasome. Furthermore, phosphorylated I kappa B alpha and pro-IL-1 beta expression decreased in the presence of fucoxanthin, suggesting that fucoxanthin can negatively regulate the priming step of inflammasome signaling. Thus, our results provide reliable evidence that fucoxanthin may serve as a key candidate in the development of potential therapeutic agents for inflammatory diseases as well as neurodegenerative diseases caused by NF-kappa B and NLRP3 inflammasome activation.